(untitled) (Journal of the College of Basic Education, 2022)
The current research aims at exploring the nature of the relationship among the variables of this research namely, self-motivation and its relationship with personal responsibility and job satisfaction in educational counselors and the contribution of (personal responsibility and job satisfaction) in the whole variance of (self-motivation). However, the sample of the study consists of (400) male and female counselors from the administrations of Education in Baghdad. The three scales of this research have been administered on this sample. By using Pearson correlational coefficient, t-test and multiple regression analysis, the results show the following:- There is a positive correlational relationship statically significant between self-motivation and both of personal responsibility and job satisfaction. - Both of personal responsibility and job satisfaction contribute in (12.5%) of the total variance of self-motivation. Psychological Counseling and Educational Guidance Department.